(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The concept of concert management in the Republic of Croatia encounters numerous obstacles in any attempt to institutionalize it. Unlike other countries in the European Union, there is no register of the concert stages, venues as well as facilities for the provision of hearing / consumption of music in the form of performances. Process management organization is incomplete, and institutions that are closely associated with such events do not carry out the classification, categorization and analysis of events that are within the concerts’ domain. Commercial music, economically far most cost-effective, is completely ignored and within the framework of cultural events not even the slightest attention is given to it. On the contrary, it is considered the music of poor quality and completely irrelevant. This paper tries to frame the mentioned genre, which includes various musical directions thateconomically bring significant benefits and help the survival of these related activities indirectly, and ultimately have a positive impact on the economy. Comparing global trends it speaks about the position of the Croatian music industry and lists the main obstacles for setting up a solid foundation for the construction of an adequate system of indexation of concert businesses that, as part of the creative industries records a meteoric economic growth. Keywords: Concert management, commercial music, music and economy